Development and fabrication of new design of latex container - Muhamad Sharif Bin Zainudin (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
The main objective of this study is to propose a new design of latex container that has cover for replace the existing latex container based on questionnaire and research.